2019
DOI: 10.18004/anales/2019.052.03.47-052
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Variables. Department of Neurology, Hospital de Clínicas from 2016 to 2018

Abstract: En el mundo hay unos 50 millones de personas con epilepsia. En países de ingresos bajos y medianos sugieren una proporción mucho mayor, entre 7 y 14 por 1000 personas. Las poblaciones pobres y las que viven en situaciones de vulnerabilidad, en particular en los países de ingresos bajos y medianos, soportan una carga desproporcionadamente alta; lo que supone una amenaza para la salud pública y el desarrollo económico y social. 1 Por el que el propósito de estudio fue conocer la característica epidemiológica de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Focal seizures are the predominant type worldwide, constituting up to two-thirds of epilepsies cases ( 24 ). According to our study, González et al ( 23 ) observed that 63.34% of patients with epilepsy presented with focal seizures. In contrast, the Argentine study has shown that seizures were generalized in 37 (58.0%) and focal in 24 (38.0%) patients with epilepsy ( 21 ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Focal seizures are the predominant type worldwide, constituting up to two-thirds of epilepsies cases ( 24 ). According to our study, González et al ( 23 ) observed that 63.34% of patients with epilepsy presented with focal seizures. In contrast, the Argentine study has shown that seizures were generalized in 37 (58.0%) and focal in 24 (38.0%) patients with epilepsy ( 21 ).…”
Section: Discussionsupporting
confidence: 55%
“…In the Argentine study, the prevalence rate of epilepsy was 5.3/1,000 for male patients and 7.1/1,000 for female patients ( 21 ). González et al ( 23 ) have analyzed patients with epilepsy in Paraguay found 51.9% of male patients. Moreover, a review study considering North, Central, and South America, Europe, and Asia, between 1985 and 2007 ( 24 ) has found a higher prevalence rate of epilepsy in men than in women.…”
Section: Discussionmentioning
confidence: 99%